Geoid determination using band limited airborne horizontal gravimetric data. Issue 2 (4th May 2022) - Deng, Kailiang; Chang, Guobin; Huang, Motao; Zeng, Huaien; Chen, Xin
ABSTRACT: Airborne vector gravimetric data have become increasingly available. A general band-limited horizontal boundary value problem using horizontal components of these vector gravimetric data is formulated and solved to compute regional geoid. The disturbing potential on the geoid is determined directly using the data in the air. This one-step approach is permitted by exploiting the following: 1) band-limited property of both the disturbing potential and the data; 2) the orthogonality of the horizontal components of the gravity vector; and 3) the additive rule of the spherical functions. Then geoidal undulations can be readily obtained according to the Bruns formula.